Emergent laparotomy and temporary abdominal closure for the cirrhotic patient - Loftus, Tyler J. (J Surg Res, 2016)
BACKGROUND: Temporary abdominal closure (TAC) may be performed for cirrhotic patients undergoing emergent laparotomy. The effects of cirrhosis on physiologic parameters, resuscitation requirements, and outcomes following TAC are unknown. We hypothesized that cirrhotic TAC patients would have different resuscitation requirements and worse outcomes than noncirrhotic patients. METHODS: We performed a 3-year retrospective cohort analysis of 231 patients managed with TAC following emergent laparotomy for sepsis, trauma, or abdominal compartment syndrome. All patients were initially managed with negative pressure wound therapy (NPWT) TAC with intention for planned relaparotomy and sequential abdominal closure attempts at 24- to 48-h intervals. RESULTS: At presentation, cirrhotic patients had higher incidence of acidosis (33% versus 17%) and coagulopathy (87% versus 54%) than noncirrhotic patients. Forty-eight hours after presentation, cirrhotic patients had a persistently higher incidence of coagulopathy (77% versus 44%) despite receiving more fresh frozen plasma (10.8 units versus 4.4 units). Cirrhotic patients had higher NPWT output (4427 mL versus 2375 mL) and developed higher vasopressor infusion rates (57% versus 29%). Cirrhotic patients had fewer intensive care unit-free days (2.3 versus 7.6 days) and higher rates of multiple organ failure (64% versus 34%), in-hospital mortality (67% versus 21%), and long-term mortality (80% versus 34%) than noncirrhotic patients. CONCLUSIONS: Cirrhotic patients managed with TAC are susceptible to early acidosis, persistent coagulopathy, large NPWT fluid losses, prolonged vasopressor requirements, multiple organ failure, and early mortality. Future research should seek to determine whether TAC provides an advantage over primary fascial closure for cirrhotic patients undergoing emergency laparotomy.